Existence, Uniqueness and Stability Results of Fractional Volterra-Fredholm Integro Differential Equations of psi-Hilfer Type - Hamoud, Ahmed A.; Sharif, Abdulrahman A.; Ghadle, Kirtiwant P. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, we establish some new conditions for the existence and uniqueness of solutions for a class of nonlinear ψ-Hilfer fractional Volterra-Fredholm integro differential equations with boundary conditions. In addition, the Ulam-Hyers stability for solutions of the given problem are also discussed. The desired results are proved by using generalized Gronwall inequality, aid of fixed point theorems due to Banach and Schauder in weighted spaces.